2008
DOI: 10.1002/pmic.200701001
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic approach to identify differentially expressed plasma proteins between the fed and prolonged fasted states

Abstract: Prolonged fasting is characterized by consecutive phases, a short period of adaptation (phase 1), phase 2 (P2) characterized by fat oxidation, and phase 3 (P3) during which energy requirements are mostly derived from increased protein utilization. At this latter stage, food seeking behavior is induced. Very few circulating biomolecules have been identified that are involved in the response to prolonged fasting. To this end, rat plasma samples were compared by a proteomic approach, using 2-DE. The results revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 55 publications
6
24
0
Order By: Relevance
“…3; Tables S1 and S2), of which five had not been reported in phase 3 fasting rats18. Among these ten downregulated proteins, most are known to be involved in the regulation of energy balance19; they also play a role in insulin resistance and lipid metabolism, immunity and inflammation, and bone metabolism2021; they are furthermore linked with cardiovascular risks and haemostasis, liver failure, and renal pathologies2122.…”
Section: Resultsmentioning
confidence: 99%
“…3; Tables S1 and S2), of which five had not been reported in phase 3 fasting rats18. Among these ten downregulated proteins, most are known to be involved in the regulation of energy balance19; they also play a role in insulin resistance and lipid metabolism, immunity and inflammation, and bone metabolism2021; they are furthermore linked with cardiovascular risks and haemostasis, liver failure, and renal pathologies2122.…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with this study, proteomic analysis showed decreased plasma DBP and reduced liver DBP mRNA concentrations during prolonged fasting. 23 Independent of the precipitation method we used, a partial co-precipitation of DBP, VLDL plus LDL particles was observed. This finding is in line with the results obtained by HPGPC and ultracentrifugation.…”
Section: Discussionmentioning
confidence: 99%
“…During PIII, energy expenditure increases again (Le Maho et al, 1981;Cherel et al, 1994b) along with glucocorticoid (GC) levels and non-reproductive behaviour (Kitaysky et al, 1999;Robin et al, 2001;Groscolas et al, 2008). This gradual reallocation of energy towards soma preservation rather than current reproduction results from a complex network of metabolic and (neuro-) hormonal changes called the 're-feeding signal' (Bertile et al, 2009;Groscolas and Robin, 2001;Minokoshi et al, 2004;Groscolas et al, 2008;Spée et al, 2010), and is expected to lead to the restoration of adult body condition at the expense of reproductive success.…”
Section: Introductionmentioning
confidence: 99%